This preview shows page 1. Sign up to view the full content.
Unformatted text preview: roblems] (b) Now, for function composition all you need to remember is that we are going to plug the
second function listed into the first function listed. If you can remember that you should always
be able to write down the basic formula for the composition.
Here is this function composition. ( f o g )( x) = f é g ( x )ù
= f [ 2 x - 1] Now, notice that since we’ve got a formula for g ( x ) we went ahead and plugged that in first.
Also, we did this kind of function evaluation in the first section we looked at for functions. At
the time it probably didn’t seem all that useful to be looking at that kind of function evaluation,
yet here it is.
Let’s finish this problem out. © 2007 Paul Dawkins 192 http://tutorial.math.lamar.edu/terms.aspx College Algebra ( f o g )( x) = f é g ( x )ù
= f [ 2 x - 1]
= 2 + 3 ( 2 x - 1) - ( 2 x - 1) 2 = 2 + 6 x - 3 - ( 4 x 2 - 4 x + 1)
= -1 + 6 x - 4 x 2 + 4 x - 1
= -4 x 2 + 10 x - 2 Notice that this is very different from the multiplication! Remember that function composition is
View Full Document
- Spring '12